2018
DOI: 10.1016/j.fsi.2018.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Distinct β-glucan molecules modulates differently the circulating cortisol levels and innate immune responses in matrinxã (Brycon amazonicus)

Abstract: This study investigated the effects of two β-glucan molecules with different purities and isolated by different biotechnological processes on the immune response of matrinxã (Brycon amazonicus) prior and after challenge with Aeromonas hydrophila. In this sense, we evaluated serum cortisol and plasma glucose levels, the number of leukocytes (lymphocytes, neutrophils and monocytes), as well as the respiratory activity of leukocytes prior to, 6 and 24 h post infection (hpi). During 15 days, fish were fed with die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
3
2
0
Order By: Relevance
“…However, it is also possible that the silkrose treatment itself causes a decrease in serum cortisol levels, as the treatment induced a significant decrease in serum cortisol levels even in yellowtail that had not been infected with many parasites. In agreement with the current result, naturally derived polysaccharides, such as those from Astralagus propinquus [53], Ulva intestinalis [54], Gracilariopsis persica [54], as well as β-glucan [55,56], have also been found to be associated with the reduction of serum cortisol level in various teleost species. These previous studies, however, did not establish the underlying mechanism of this cortisol-lowering effect.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is also possible that the silkrose treatment itself causes a decrease in serum cortisol levels, as the treatment induced a significant decrease in serum cortisol levels even in yellowtail that had not been infected with many parasites. In agreement with the current result, naturally derived polysaccharides, such as those from Astralagus propinquus [53], Ulva intestinalis [54], Gracilariopsis persica [54], as well as β-glucan [55,56], have also been found to be associated with the reduction of serum cortisol level in various teleost species. These previous studies, however, did not establish the underlying mechanism of this cortisol-lowering effect.…”
Section: Discussionsupporting
confidence: 91%
“…This condition, called immunosuppression, increases the susceptibility of the fish body to the development of bacterial and viral infections [50]. The scientific literature contains data confirming the thesis that β-glucan administered with the diet contributes to the reduction in cortisol secretion by intrarenal cells in fish [31,51]. The presented work also confirmed the above thesis.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, MacroGard ® , a commercial product extracted from S. cerevisiae containing a minimum of 60% β-1,3/1,6-glucans, was the source used. Some studies using the same supplementation concentrations as the present study have demonstrated the effect of dietary yeast β-glucans on the modulation of RBC counts and hemoglobin, lysozyme, total protein, albumin, globulin, total cholesterol, and glucose concentrations (Cao et al 2019, Ghaedi et al 2015, Montoya et al 2018, Talpur et al 2014. Meanwhile, some studies have also reported the lack of effects on hematological, immunological, ED C.S.…”
Section: Effect Of β-Glucans On Hematological Immunological and Bioch...supporting
confidence: 55%